Microsomal chitinase activity from Candida albicans - Dickinson, Keith; Keer, Valerie; Hitchcock, Christopher A.; Adams, David J. (Biochimica et biophysica acta, 1991)
Chitinase (E.C. 3.2.1.14) was characterized in microsomal fractions from yeast cells of Candida albicans. Following six washes with buffer (50 mM Bis-Tris · Cl, pH 6.5), enzyme activity of microsomes fell markedly to 0.3% of total and 6% of the specific activity detected in the low-speed supernatant (9000 × g) of a cell lysate. An apparently zymogenic, microsomal chitinase activity became more readily detectable with washing and after six washes enzyme activity was activated 1.7-fold following pre-incubation with trypsin. The following properties of microsomal chitinase were closely comparable with those for cytosolic chitinase (indicated in parentheses): Km = 2.1 mg chitin per ml (2.9 mg chitin per ml); temperature optimum = 45°C (45°C); inhibition by allosamidin competitive, Ki = 0.29 μM (competitive, Ki = 0.23 μM). A range of detergents solubilized and activated microsomal chitinase in a highly specific manner. Following density gradient centrifugation of microsomes, chitinase was distributed approximately evenly throughout the gradient suggesting that microsomal chitinase is not associated exclusively with any one membrane component. The possible morphogenetic role of microsomal chitinase is discussed in relation to the potential of this enzyme as a target for highly specific antifungal agents.